If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 2)(x + -3) = 2 Reorder the terms: (2 + x)(x + -3) = 2 Reorder the terms: (2 + x)(-3 + x) = 2 Multiply (2 + x) * (-3 + x) (2(-3 + x) + x(-3 + x)) = 2 ((-3 * 2 + x * 2) + x(-3 + x)) = 2 ((-6 + 2x) + x(-3 + x)) = 2 (-6 + 2x + (-3 * x + x * x)) = 2 (-6 + 2x + (-3x + x2)) = 2 Combine like terms: 2x + -3x = -1x (-6 + -1x + x2) = 2 Solving -6 + -1x + x2 = 2 Solving for variable 'x'. Reorder the terms: -6 + -2 + -1x + x2 = 2 + -2 Combine like terms: -6 + -2 = -8 -8 + -1x + x2 = 2 + -2 Combine like terms: 2 + -2 = 0 -8 + -1x + x2 = 0 Begin completing the square. Move the constant term to the right: Add '8' to each side of the equation. -8 + -1x + 8 + x2 = 0 + 8 Reorder the terms: -8 + 8 + -1x + x2 = 0 + 8 Combine like terms: -8 + 8 = 0 0 + -1x + x2 = 0 + 8 -1x + x2 = 0 + 8 Combine like terms: 0 + 8 = 8 -1x + x2 = 8 The x term is -1x. Take half its coefficient (-0.5). Square it (0.25) and add it to both sides. Add '0.25' to each side of the equation. -1x + 0.25 + x2 = 8 + 0.25 Reorder the terms: 0.25 + -1x + x2 = 8 + 0.25 Combine like terms: 8 + 0.25 = 8.25 0.25 + -1x + x2 = 8.25 Factor a perfect square on the left side: (x + -0.5)(x + -0.5) = 8.25 Calculate the square root of the right side: 2.872281323 Break this problem into two subproblems by setting (x + -0.5) equal to 2.872281323 and -2.872281323.Subproblem 1
x + -0.5 = 2.872281323 Simplifying x + -0.5 = 2.872281323 Reorder the terms: -0.5 + x = 2.872281323 Solving -0.5 + x = 2.872281323 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '0.5' to each side of the equation. -0.5 + 0.5 + x = 2.872281323 + 0.5 Combine like terms: -0.5 + 0.5 = 0.0 0.0 + x = 2.872281323 + 0.5 x = 2.872281323 + 0.5 Combine like terms: 2.872281323 + 0.5 = 3.372281323 x = 3.372281323 Simplifying x = 3.372281323Subproblem 2
x + -0.5 = -2.872281323 Simplifying x + -0.5 = -2.872281323 Reorder the terms: -0.5 + x = -2.872281323 Solving -0.5 + x = -2.872281323 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '0.5' to each side of the equation. -0.5 + 0.5 + x = -2.872281323 + 0.5 Combine like terms: -0.5 + 0.5 = 0.0 0.0 + x = -2.872281323 + 0.5 x = -2.872281323 + 0.5 Combine like terms: -2.872281323 + 0.5 = -2.372281323 x = -2.372281323 Simplifying x = -2.372281323Solution
The solution to the problem is based on the solutions from the subproblems. x = {3.372281323, -2.372281323}
| 1/4x-2/3=y | | 3(k+3)=6(k-4) | | -15--4= | | -16x+5=6+5x | | 2x-1/x-7 | | 38s-4-6=0 | | 2(4-3X)=5(2-X) | | -9h++12h= | | ln(4x+2)=2.8 | | 384-400x=-56x^2-x | | 4x+9=13x | | 384-400x=-56x^2+384 | | y=(-1.56)100+95 | | y=(-1.56)x+95 | | 45/14 | | 8(x^2-50x+48)=0 | | A=r(c/2) | | 4y=5.12 | | F(x)=(1/6x)^5 | | 100x+7=57 | | F(x)=(1/6x)5 | | F(x)=(16x)5 | | 3m+5n+7m+9n= | | -2x-1=-4x | | -3(2y-7x)-y= | | 8x^2+6x-40=0 | | 3x-9=1.5x+6 | | 6y^2=96 | | 6x^2+6x-40=0 | | (5x+4)(x+5)= | | 4y+5y-2y=49 | | k=8k+2k |